Production Structure, Yield Dynamics, and Technical Efficiency of Ginger Farming Systems in Sierra Leone - Ngegba, Mohamed Paul; Amara, Vandi; Kargbo, James; Mansaray, Suffian (European Journal of Applied Sciences, 2026)
Ginger production plays an increasingly important role in rural livelihoods in Sierra Leone, yet empirical evidence on its structural characteristics, productivity dynamics, and efficiency performance remains limited. This study examines the production structure, yield determinants, spatial productivity differences, and technical efficiency of ginger farming systems in two major producing districts Kenema and Kailahun. Data were collected from 160 smallholder farmers using a structured questionnaire and analyzed using descriptive statistics, chi-square tests, t-tests, multiple regression, and efficiency analysis. Results indicate a predominantly smallholder system characterized by low educational attainment and small farm sizes averaging one acre, with balanced gender participation. Yield analysis reveals significant spatial variation, with Njaluahun Chiefdom outperforming Nongowa Chiefdom (t = -5.21, p < 0.001). Regression results show that education, household labor, organic input use, and access to extension services significantly influence productivity. Efficiency analysis further indicates that only 11.2% of farmers operate at full efficiency, while the majority remain below optimal performance, reflecting substantial productivity gaps. Overall, the findings demonstrate that ginger production is constrained more by inefficiencies in resource use and weak knowledge systems than by resource scarcity. Strengthening extension services and promoting efficient input use are therefore critical for unlocking productivity gains and improving smallholder livelihoods.